Literature Review to Finding the Originality of Research : (A Note for Legal Researchers) - Sjafei , Saleh (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
A riterature review is closely related to previous research results (articles) published by researchers in reputable national and international journals. Literature reviews are almost never conducted by legal researchers during undergraduate, postgraduate, and doctoral legal studies in Indonesia, particularly in legal education at the university where I work. This article aims to share how a literature review is conducted to connect research to a broader and more sustainable dialectical space in the literature on a topic, filling gaps, and expanding previous research. To disseminate scientific knowledge, a literature review can provide researchers with an additional framework for determining research impotence and a benchmark for comparing research findings with other findings. This research model is based more on previous research related to public perceptions of female ulama (Islamic leader) in Aceh. The position of ulama in the community concerned is seen as a status (socio-political position) that enables muslims to achieve charismatic, traditional, and rational authority. The issue of the ulama's position in society has increasingly received attention from various levels of society, especially since Islamic legal politics was socialized and used as a means to change the image and views of the outside community regarding Islamic practices in a society undergoing a transitional process. This includes groups of women who have the potential to occupy the position of ulama.